RESPONSIBILITY OF GUARDIANS AND TRUSTEES IN ACCORDANCE WITH THE LEGISLATION OF THE REPUBLIC OF KAZAKHSTAN - Nurakhmetova , Гүлдара Нұрахметқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2021)
The author defines the responsibility based on the exercise of the functions of guardians and trustee, the basic rules of legal regulation in accordance with the legislation of the Republic of Kazakhstan. According to the rules for the exercise of the functions of the state for custody and guardianship, the goals and objectives of guardians and trustees are defined. However, in practice, these civil legal relations give rise to big problems. In this regard, it should be paid attention to the need to regulate the legal framework that provides for the responsibility of guardians and trustees. For example, since the powers and responsibilities of custodians and guardians are not properly regulated, there is a problem of restricting the rights of capable or disabled adults and thousands of minors, including orphans, children left without parental care, children with difficult living conditions and those left without housing, who remain at a low level of society. Since the above-mentioned practical problem is inherent in our country and the judicial system, the problem has not been fully investigated to date, which implies the novelty of this article. Questions arise as to why the duties and powers of guardians and trustees are not approved in the legal field. Why is there no liability? Due to the fact that the norms of law are not applied and observed accordingly, the reasons for not exercising the rights of persons under custody and guardianship granted by the legislation remain an actual problem. Subject of the work: responsibility of guardians and trustees in accordance with the legislation of the Republic of Kazakhstan and its legal basis. Methodological foundations of the article. The legal method contributed to the identification of the relationship of research work with other legal relations, the formal - dogmatic method - understanding of the system and structures of fundamental legal rules that are formed in the process of development and implemented in specific legal systems, the analysis - to a comprehensive review of their relations, dividing them into several components.